Research Progress on the Mechanism of Acupuncture Treatment of Ischemic Stroke Based on the Space Construction of Nerve-vascular Unit - LI Mengxing; WNAG Yu; LI Zhen; LIU Fang; SHI Kejian (康复学报)
ObjectiveTo explore the research progress of the mechanism of acupuncture in the treatment of ischemic stroke (IS), based on the changes in the spatial architecture of neurovascular unit (NVU) after cerebral ischemia.MethodsThe research result of NVU in the field of neuroscience and research status of acupuncture treatment of IS was summarized by referring to domestic and foreign literature. It is mainly discussed on acupuncture research from the structural function of NVU to the spatial structure changes in IS, with neurons as the one-dimensional target, neurons, brain microvascular endothelial cells (BMEC) as the two-dimensional target, and with neurons, BMEC and glial cells as the multi-dimensional target.ResultsMost of the previous studies on acupuncture treatment of IS only stayed at a single level of neuron or angiogenesis regulation, and rarely involved the research on the overall NVU and the interaction among its components. Meanwhile there was a lack of systematic treatment plans with NVU space construction as the entry point both for basic and clinical studies. Acupuncture treatment of IS has the advantages and characteristics of multi-component, multi-target and multi-link effect, which is consistent with traditional Chinese medicine (TCM) syndrome differentiation and treatment, and has always been a hot research topic in the fields of TCM and neuroscience. Acupuncture could inhibit neuronal apoptosis, regulate synaptic plasticity, and reorganize and compensate brain functional network and induce neovascularization, regulate cerebral blood flow, and coordinate the coupling between nerves and blood vessels. It could also regulate the energy metabolism of astrocytes, inhibit excitatory toxicity and inflammatory response, and coordinate the interaction among neurons, BMEC and glial cells based on the bidirectional regulation effect. The selection of targeted interventions among many targets could provide a direction to elucidate the possible material basis and effective target of acupuncture to reduce cerebral ischemic injury.ConclusionThe mechanism of acupuncture treatment of cerebral ischemia is closely related to NVU, which plays a synergistic neuroprotective role by bidirectional regulation of NVU spatial architecture, and it is the key to promoting functional recovery after cerebral ischemia.